Trupul cuvântului rostit. De la aer la forma sonoră - Mihăilă, Cătălina-Elena (Theatrical Research, 2024)
The Body of the Spoken Word. From air to sound form I often tell young actors or future artists that it is necessary to be aware of the phonation process and to have control over it, even if in everyday life we speak without paying attention to breathing or vocalization. Thus, the dramatic artist must change his type of breathing and be able to breathe consciously and in a controled manner, to know his voice and its qualities with which he can paint countless logical or affective nuances and to understand how the word is produced.